Bibliometric analysis and network visualization on Tuberous Sclerosis Complex (Bangladesh Journal of Medical Science, 2024)
Background: Tuberous sclerosis complex (TSC) is a rare autosomal dominant multisystem disease resulting from hyperactivation of the mammalian target of rapamycin (mTOR) signaling pathway. This study aimed to measure the quantitative impact of publications in TSC.Materials and methods: We analysed TSC literature obtained from the Scopus database using Bibliometrix R Package and VOSviewer software. Annual publication trends, most productive and collaborative authors/institutions/ countries, most cited articles, most popular journals and author’s keywords were presented using standard bibliometric indicators.Results and discussion: A total of 5375 documents on TSC were published from 1960 to December 2020, with an increasing trend. The three primary contributing writers were Curatolo P, Kwiatkowski DJ, and Thiele EA, with the United States and its institutions being the largest contributor. The research identified two of the most referenced papers as TSC’s seminal pieces. The top journals that published TSC research were medical journals, namely Journal of Child Neurology, Epilepsia, and Pediatric Neurology. mTOR inhibitor, everolimus, sirolimus, mTORC1, mTOR pathway, autophagy, inflammation, infant, intellectual disability, white matter, TSC-associated neuropsychiatric disorders, TOSCA and quality of life were relatively newer author’s keywords and may indicate the future research hotspots in TSC research.Conclusion: Over the last few decades, TSC research has grown in importance, particularly in the field of clinical medicine. Therapeutic components targeting TSC-related pathways, the utilisation of TSC as disease models and long-term safety studies will be future research areas.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 18-28